Primary pulmonary marginal zone lymphoma: an unusual cause of pulmonary infiltrates. Issue 8 (29th June 2021) - Smyth, Robert; Sloan, John Mark; Burks, Eric; Hawkins, Finn
Abstract: Primary pulmonary extra‐nodal marginal zone lymphoma of mucosa‐associated lymphoid tissue (MALT lymphoma), also known as bronchus‐associated lymphoid tissue (BALT lymphoma), is the most common primary pulmonary lymphoma but is rare (<1%) among all non‐Hodgkin lymphomas and among pulmonary neoplasms in general. We herein report the case of a 59‐year‐old male who presented with stable exertional dyspnoea and persistent lung infiltrates who was referred to our hospital for further assessment. A computed tomography (CT)‐guided core biopsy was performed showing a dense lymphoid infiltrate, with further testing revealing the diagnosis of pulmonary MALT lymphoma. This uncommon lung tumour is usually seen in older adults and typically associated with a relatively indolent course. Rituximab, an anti‐CD20 antibody, has been shown to be effective in up to 70% of cases. Abstract : A middle‐aged male presents with dyspnoea and multifocal consolidations. Biopsy shows pulmonary MALT lymphoma, a rare lung tumour.